Solid solution catalyst comprising Cu, Ce and Y for decomposing nitrous oxide and method of fabricating the same

KR103020885B1Active Publication Date: 2026-09-18KOREA INST OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
KR1020240002453
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-01-05
Publication Date
2026-09-18
Estimated Expiration
2044-01-05

Smart Images

  • Figure 112024002117203-PAT00002_ABST
    Figure 112024002117203-PAT00002_ABST
Patent Text Reader

Abstract

The present invention provides a solid solution catalyst for decomposing nitrous oxide comprising copper, cerium, and yttrium, and a method for manufacturing the same. The catalyst comprises copper, cerium, and yttrium in oxide form, respectively, wherein the molar ratio of cerium to yttrium is 1:9 to 9:1, and the copper is included in an amount of 1 to 20 weight% relative to the total weight of the catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a nitrous oxide decomposition catalyst and a method for manufacturing the same, and more specifically, to a solid solution catalyst for nitrous oxide decomposition comprising copper, cerium, and yttrium and a method for manufacturing the same. Background Technology

[0002] Nitrous oxide (N2O) is a greenhouse gas that contributes to global warming caused by ozone depletion. It accounts for the largest share of gases that cause ozone depletion and is known to have a Global Warming Potential (GWP) approximately 310 times higher than that of carbon dioxide (CO2). In 2021, the energy sector accounted for the largest share of greenhouse gas emissions at 86.9%. Emissions in the energy sector increased by 3.6% compared to 2020 due to increased production and fuel consumption, centered on the manufacturing, power generation, and transportation sectors. Nitrous oxide is also generated as a byproduct of the Selective Catalytic Reduction (SCR) reaction, which catalyzes ammonia as a reducing agent to remove nitrogen oxides (NOx) from artificial sources, including the production of nitric acid and adipic acid, and agricultural activities. Furthermore, with the shift in the energy paradigm from a conventional fossil fuel-based energy system to zero-carbon and low-carbon fuels for carbon neutrality, the use of ammonia fuel—an eco-friendly energy source particularly used as a hydrogen carrier—is expanding, leading to an increase in the generation of nitrous oxide. Consequently, various studies are being conducted to remove nitrous oxide. Among these, catalytic N2O direct decomposition technology is known, which decomposes nitrous oxide into nitrogen (N2) and oxygen (O2) using only a catalyst without the need for a separate reducing agent. However, conventional nitrous oxide direct decomposition catalysts primarily contain precious metals such as Rh, Ru, Ir, and Pd to enhance their decomposition performance. Consequently, the high cost associated with these precious metals becomes a problem, and conventional nitrous oxide direct decomposition catalysts also exhibit low thermal stability. Therefore, there is a demand for a nitrous oxide decomposition catalyst that does not use precious metals while possessing improved activity and durability. The problem to be solved

[0003] The problem that the present invention aims to solve is to provide a nitrous oxide decomposition catalyst that does not contain precious metals and does not use a separate reducing agent in a temperature range of 450 to 500°C.

[0004] Another problem that the present invention aims to solve is to provide a method for manufacturing the nitrous oxide decomposition catalyst. means of solving the problem

[0005] A solid solution catalyst for decomposing nitrous oxide according to the concept of the present invention for achieving the above objective comprises copper, cerium, and yttrium in oxide form, respectively, wherein the molar ratio of cerium to yttrium is 1:9 to 9:1, and the copper is included in an amount of 1 to 20 weight percent relative to the total weight of the catalyst.

[0006] The copper oxide is at least one of CuO, Cu2O, and CuO2, and the proportion of CuO in the total copper oxide included in the catalyst may be 60 to 100%.

[0007] The cerium oxide is at least one of CeO2 and Ce2O3, and the proportion of Ce2O3 among the total cerium oxide included in the catalyst may be 15 to 100%.

[0008] The catalyst further includes oxygen species, and among the oxygen species, surface oxygen species disposed on the surface of the catalyst may be 40% to 100% of the total oxygen species.

[0009] The oxide of the above yttrium may be Y2O3.

[0010] A method for manufacturing a nitrous oxide decomposition solid solution catalyst according to the concept of the present invention for achieving the above other objectives comprises: a step of preparing a cerium-yttrium aqueous solution by dissolving a cerium precursor and a yttrium precursor in distilled water such that the molar ratio of cerium to yttrium is 1:9 to 9:1; a step of adding nitric acid to the cerium-yttrium aqueous solution to adjust the pH of the cerium-yttrium aqueous solution to 1.9 to 2.1; a step of preparing a first slurry by adding citric acid to the cerium-yttrium aqueous solution and performing a heating process; a step of preparing a cerium-yttrium carrier by drying the first slurry and performing a first calcination process; a step of preparing a copper aqueous solution by dissolving a copper precursor in distilled water; a step of preparing a second slurry by adding the cerium-yttrium carrier to the copper aqueous solution and mixing; and a step of drying the second slurry and performing a second calcination process.

[0011] The above nitrous oxide decomposition solid solution catalyst comprises copper, cerium, and yttrium, and the copper precursor may be provided such that the copper is included in an amount of 1 to 20 weight percent relative to the total weight of the catalyst.

[0012] At least one of the above first firing and the above second firing may be carried out in an air atmosphere at a temperature of 200 to 800°C for 2 to 8 hours.

[0013] The above copper precursor is copper nitrate trihydrate (Cu(NO3) 2· 3H2O), kappa sulfate (CuSO4), kappa chloride (CuCl2), kappa oxide (CuO), kappa sulfate pentahydrate (CuSO4 4· 5H2O), kappa hydroxide (Cu(OH)2), kappa chloride dihydrate (CuCl 2· 2H2O), kappa acetate (Cu(CO2CH3)2) and kappa nitrate hydrate (Cu(NO3) 2· It can be at least one of xH2O).

[0014] The above cerium precursor is cerium nitrate hexahydrate (Ce(NO3) 3· 6H2O), cerium chloride (CeCl3), cerium sulfate (Ce2(SO4)3), cerium oxalate hydrate (Ce2(C2O4) 3· xH2O), cerium acetate hydrate (Ce(CH3CO2) 3· xH2O), cerium hydroxide (Ce(OH)4), cerium oxide (CeO2) and cerium carbonate hydrate (Ce2(CO3)) 3· It can be at least one of xH2O).

[0015] The above yttrium precursor is nitrate hexahydrate (Y(NO3) 3· 6H2O), yttrium chloride (YCl3), yttrium acetate hydrate ((CH3CO2)3Y · xH2O), yttrium nitrate tetrahydrate (Y(NO3) 3· 4H2O), yttrium oxide (Y2O3) and yttrium chloride hexahydrate (YCl 3· It may be at least one of 6H2O. Effects of the invention

[0016] The solid solution catalyst for decomposing nitrous oxide according to the present invention can directly decompose and remove nitrous oxide in the 450-500°C range without a separate reducing agent. Since the solid solution catalyst does not contain precious metals and is a non-precious metal-based catalyst, manufacturing costs can be reduced. The solid solution catalyst can have durability against nitric oxide (NO) present in exhaust gas.

[0017] In the method for manufacturing a catalyst for nitrous oxide decomposition according to the present invention, the physicochemical properties of the catalyst can be controlled by adding yttrium. This allows for the production of a catalyst for nitrous oxide decomposition having excellent performance. Brief explanation of the drawing

[0018] FIG. 1 is a schematic diagram showing a solid solution catalyst for nitrous oxide decomposition according to embodiments of the present invention. FIG. 2 shows the direct decomposition of nitrous oxide by catalysts prepared according to Preparation Example 2 and Comparative Preparation Examples 2 and 3 of the present invention. · This is a graph showing the results of the removal performance evaluation. FIG. 3 is a graph showing the results of evaluating the direct decomposition and removal performance of nitrous oxide by catalysts prepared according to Manufacturing Example 2 and Comparative Manufacturing Examples 4 to 7 of the present invention. Figure 4 is a graph showing the results of the evaluation of the direct decomposition and removal performance of nitrous oxide by catalysts prepared according to Manufacturing Examples 1 to 3 and Comparative Manufacturing Example 1 of the present invention. FIG. 5 is a graph showing the X-ray diffraction patterns (XRD patterns) of catalysts prepared according to Preparation Examples 1 to 3 and Comparative Preparation Example 1 of the present invention. FIG. 6 is a graph showing the selected area electron diffraction patterns (SAED patterns) of catalysts prepared according to Preparation Examples 1 to 3 and Comparative Preparation Example 1 of the present invention. FIG. 7 shows the oxygen species (O) corresponding to the sum of surface-adsorbed oxygen to the total oxygen species among the oxygen species, using XPS analysis on catalysts prepared according to Preparation Examples 1 to 3 and Comparative Preparation Example 1 of the present invention to confirm the type and distribution of oxygen species formed on the surface of the catalyst. V This is a graph showing the ratio of ). FIG. 8 shows the cerium (Ce) corresponding to the sum of the oxidation values ​​of +3 for the total cerium among the cerium oxides, using XPS analysis on catalysts prepared according to Preparation Examples 1 to 3 and Comparative Preparation Example 1 of the present invention to confirm the type and distribution of cerium oxide formed on the surface of the catalyst. 3+ This is a graph showing the ratio of ). FIG. 9 shows the copper (Cu) corresponding to the sum of oxidation values ​​of +2 for total copper among the copper oxides, using XPS analysis on catalysts prepared according to Preparation Examples 1 to 3 and Comparative Preparation Example 1 of the present invention to confirm the type and distribution of copper oxide formed on the surface of the catalyst. 2+ This is a graph showing the ratio of ). Figure 10 is a graph showing the desorption of oxygen according to temperature using O2-TPD analysis for catalysts prepared according to Preparation Examples 1 to 3 and Comparative Preparation Example 1 of the present invention to confirm the oxygen adsorption / desorption characteristics of the catalyst. Figure 11 is a graph showing the amount of hydrogen consumed according to temperature using H2-TPR analysis for catalysts prepared according to Preparation Examples 1 to 3 and Comparative Preparation Example 1 of the present invention to confirm the redox characteristics of the catalyst. FIG. 12 is a graph showing the results of evaluating the influence of nitric oxide (NO) on the direct decomposition and removal of nitrous oxide by the catalyst prepared according to Example 2 of the present invention. Specific details for implementing the invention

[0019] Hereinafter, the present invention will be described in detail with reference to the attached drawings so that those skilled in the art can easily implement the invention.

[0021] FIG. 1 is a schematic diagram showing a solid solution catalyst for nitrous oxide decomposition according to embodiments of the present invention.

[0022] Referring to FIG. 1, the solid solution catalyst (100) for decomposing nitrous oxide according to the present example comprises copper (Cu), cerium (Ce), and yttrium (Y) in oxide form, respectively. The solid solution catalyst (100) according to the present invention may also be referred to as a 'copper-cerium-yttrium solid solution catalyst'. In the solid solution catalyst (100), the molar ratio of cerium to yttrium is 1:9 to 9:1, and preferably 1:1. The copper is included in an amount of 1 to 20 weight percent relative to the total weight of the catalyst. The solid solution catalyst (100) is a cerium-yttrium oxide carrier (Ce c O d Copper oxides (Cu-Y2O3) on the surface of -Y2O3) a O b It may have a combined form. In the solid solution catalyst (100), the oxide of yttrium may be Y2O3. The oxide of yttrium may contain oxygen vacancies (V0). Since the solid solution catalyst (100) contains the oxide of yttrium, if a portion (P1) of the cerium-yttrium oxide carrier is magnified as in FIG. 1, oxygen vacancies (V0) may be present.

[0023] The above copper oxide (Cu a O b ) may be at least one of CuO, Cu2O, and CuO2. The oxidation value of the copper included in the catalyst may be +1, +2, or +4. The oxidation value of copper in CuO is +2. The oxidation value of copper in Cu2O is +1. The oxidation value of copper in CuO2 is +4. The proportion of CuO (i.e., the proportion of copper corresponding to an oxidation value of +2) in the total copper oxide included in the catalyst may be 60 to 100%.

[0024] The above cerium oxide (Ce c O d) may be at least one of CeO2 and Ce2O3. The oxidation value of cerium included in the catalyst may be +3 or +4. The oxidation value of cerium in Ce2O3 is +2. The oxidation value of cerium in CeO2 is +4. The proportion of Ce2O3 (i.e., the proportion of cerium corresponding to an oxidation value of +3) in the total cerium oxide included in the catalyst may be 15 to 100%.

[0025] The catalyst further includes oxygen species, and among the oxygen species, surface oxygen species disposed on the surface of the catalyst may be 40% to 100% of the total oxygen species.

[0026] The solid solution catalyst (100) for decomposing nitrous oxide according to the present invention can directly decompose and remove nitrous oxide in the 450-500°C range without a separate reducing agent. Since the solid solution catalyst (100) does not contain precious metals and is a non-precious metal catalyst, manufacturing costs can be reduced. The solid solution catalyst (100) can have durability against nitric oxide (NO) present in exhaust gas.

[0027] A method for preparing a nitrous oxide decomposition solid solution catalyst according to embodiments of the present invention comprises the steps of: preparing a cerium-yttrium aqueous solution by dissolving a cerium precursor and a yttrium precursor in distilled water such that the molar ratio of cerium to yttrium is 1:9 to 9:1; adding nitric acid to the cerium-yttrium aqueous solution to adjust the pH of the cerium-yttrium aqueous solution to 1.9 to 2.1; preparing a first slurry by adding citric acid to the cerium-yttrium aqueous solution and performing a heating process; preparing a cerium-yttrium carrier by drying the first slurry and performing a first calcination process; preparing a copper aqueous solution by dissolving a copper precursor in distilled water; preparing a second slurry by adding the cerium-yttrium carrier to the copper aqueous solution and mixing; and drying the second slurry and performing a second calcination process.

[0028] The above nitrous oxide decomposition solid solution catalyst comprises copper, cerium, and yttrium, and the copper precursor may be provided such that the copper is included in an amount of 1 to 20 weight percent relative to the total weight of the catalyst.

[0029] At least one of the above first firing and the above second firing may be carried out in an air atmosphere at a temperature of 200 to 800°C for 2 to 8 hours.

[0030] The above copper precursor is copper nitrate trihydrate (Cu(NO3) 2· 3H2O), kappa sulfate (CuSO4), kappa chloride (CuCl2), kappa oxide (CuO), kappa sulfate pentahydrate (CuSO4 4· 5H2O), kappa hydroxide (Cu(OH)2), kappa chloride dihydrate (CuCl 2· 2H2O), kappa acetate (Cu(CO2CH3)2) and kappa nitrate hydrate (Cu(NO3) 2· It can be at least one of xH2O).

[0031] The above cerium precursor is cerium nitrate hexahydrate (Ce(NO3) 3· 6H2O), cerium chloride (CeCl3), cerium sulfate (Ce2(SO4)3), cerium oxalate hydrate (Ce2(C2O4) 3· xH2O), cerium acetate hydrate (Ce(CH3CO2) 3· xH2O), cerium hydroxide (Ce(OH)4), cerium oxide (CeO2) and cerium carbonate hydrate (Ce2(CO3)) 3· It can be at least one of xH2O).

[0032] The above yttrium precursor is nitrate hexahydrate (Y(NO3) 3· 6H2O), yttrium chloride (YCl3), yttrium acetate hydrate ((CH3CO2)3Y ·xH2O), yttrium nitrate tetrahydrate (Y(NO3) 3· 4H2O), yttrium oxide (Y2O3) and yttrium chloride hexahydrate (YCl 3· It may be at least one of 6H2O.

[0033] In the present invention, X-ray diffraction pattern (XRD pattern) and selected area electron diffraction pattern (SAED pattern) analysis are used as methods to analyze the structural characteristics of a catalyst. Through XRD and SAED pattern analysis, changes in the structural characteristics of a copper-cerium catalyst due to the addition of yttrium can be investigated.

[0034] In the present invention, X-ray photoelectron spectroscopy (XPS) analysis is used as a method to analyze the oxidation states and oxygen species of copper, cerium, and yttrium supported on a catalyst. Through XPS analysis, elemental peaks on the catalyst surface can be separated based on the intrinsic binding energy of elemental oxides using the Gaussian-Lorentzian method, thereby allowing for the analysis of the types of oxides present on the catalyst surface and their distribution ratios. As a result of the XPS analysis, the effect of c-type Y2O3 oxide on the oxidation characteristics and oxygen species characteristics of copper and cerium can be investigated following the addition of yttrium to the present invention.

[0035] In the present invention, the oxygen adsorption / desorption characteristics and redox capabilities of the copper-cerium catalyst with added yttrium can be investigated through O2-TPD (temperature programmed desorption) and H2-TPR (temperature programmed reduction) analyses as a method to confirm the oxygen adsorption / desorption characteristics and redox capabilities of the catalyst.

[0036] In the present invention, a copper-cerium solid solution catalyst was prepared as a comparative manufacturing example. The copper-cerium solid solution catalyst is prepared by supporting copper on a cerium oxide support to prepare a mixed slurry, followed by drying and calcination.

[0037] A copper-cerium-yttrium solid solution catalyst according to an embodiment of the present invention is prepared by supporting copper on a cerium-yttrium oxide carrier to prepare a mixed slurry, and then drying and calcining it.

[0038] In the preparation examples of the present invention, copper precursor is copper nitrate trihydrate (Cu(NO3) 2· 3H2O (Junsie Chemical Co.) is used, and cerium nitrate hexahydrate (Ce(NO3)) is used as a cerium precursor. 3· 6H2O (Sigma Aldrich) was used, and yttrium nitrate hexahydrate (Y(NO3)) was used as the yttrium precursor. 3· 6H2O (Sigma Aldrich) was used. In the preparation example of the present invention, the copper precursor was included so that the copper could be contained in an amount of 1.0 to 20.0 weight% of the total weight of the catalyst, and the cerium precursor and the yttrium precursor were included so that the molar ratio of cerium to yttrium was 1:9 to 9:1.

[0039] Specific examples of the preparation of the copper-cerium-yttrium solid solution catalyst of the present invention are as follows.

[0040] <Manufacturing Example>

[0041] A cerium-yttrium aqueous solution is prepared by dissolving cerium precursors and yttrium precursors in distilled water in amounts such that the molar ratio of cerium to yttrium is 1:9 to 9:1. In this case, cerium nitrate hexahydrate (Ce(NO3)) is used as the cerium precursor. 3· 6H2O), and yttrium nitrate hexahydrate (Y(NO3)) as the yttrium precursor 3·6H2O) is used. Subsequently, 0.5 M nitric acid (HNO3, Junsie Chemical Co.) is added to the cerium and yttrium precursors to adjust the pH of the cerium-yttrium aqueous solution to 1.9 to 2.1. Citric acid (C6H8O7, Sigma Aldrich), equivalent to 1.5 times the sum of the molar values ​​of the cerium precursor and the yttrium precursor, is added to the cerium-yttrium aqueous solution and stirred to prepare a first slurry. Then, to remove residual moisture contained in the catalyst micropores, the first slurry is dried using a dryer for at least one day. A heat treatment process (or primary calcination process) is performed on the first slurry after the drying process is completed under an air atmosphere to prepare a cerium-yttrium carrier (or cerium-yttrium solid solution). Then, a copper precursor equivalent to 10 wt% copper is dissolved in distilled water to prepare a copper aqueous solution. In this case, the copper precursor is copper nitrate trihydrate (Cu(NO3) 2· 3H2O) is used. Subsequently, a second slurry is prepared by mixing and stirring with a cerium-yttrium solid solution. Then, to remove residual moisture contained in the catalyst micropores, the second slurry is dried using a dryer for at least one day. After the drying process is completed, a heat treatment process (or a secondary calcination process) is performed on the second slurry under an air atmosphere.

[0042] Considering the decomposition performance and energy efficiency for nitrous oxide, the heat treatment process of the copper-cerium-yttrium solid solution catalyst is carried out in an air atmosphere at a temperature of 200 to 800°C for 2 to 8 hours, preferably at a temperature of 500°C for 5 hours. This heat treatment process can be carried out in a tube furnace, a convection furnace, a grate furnace, etc.

[0043] In the method for preparing a solid solution catalyst for nitrous oxide decomposition according to the present invention, by adding yttrium, the oxygen vacancies between copper atoms and cerium atoms can be increased while maintaining the lattice oxygen of cerium oxide within the solid solution catalyst (100). Copper (Cu) corresponding to the sum of the oxidation states of the total copper among the copper oxides (Cu 2+ The ratio of ) can be controlled to 60% or more. In addition, when manufacturing a copper-cerium-yttrium solid solution catalyst using an impregnation method, the copper content as the main catalyst can be added at 1 to 20 weight% in terms of the weight ratio of the catalyst to produce a copper-cerium-yttrium solid solution catalyst. In addition, the copper-cerium-yttrium solid solution catalyst can be manufactured by varying the heat treatment temperature of the copper from 200 to 800°C. In this way, the physicochemical properties of the solid solution catalyst (100) can be controlled. This allows for the production of a solid solution catalyst for nitrous oxide decomposition with excellent performance. Furthermore, by varying the molar ratio of cerium and yttrium in the cerium-yttrium carrier, a nitrous oxide decomposition and removal performance of 83% or more can be exhibited at 450°C or higher.

[0044] In addition, the copper-cerium-yttrium solid solution catalyst according to the present invention can be used by processing it into a particulate or monolithic form with a small amount of binder, manufacturing it into a plate, pellet, etc., or coating it onto a carrier processed in such a form.

[0045] Furthermore, the copper-cerium-yttrium solid solution catalyst according to the present invention can be practically applied by coating structures such as metal plates, metal fibers, ceramic filters, honeycombs, and glass tubes, or air purifiers, interior decorations, interior and exterior materials, and wallpaper, and can also be used in industrial processes where flue gas containing ammonia and nitric oxide is generated.

[0046] Specific embodiments of the present invention will be described in detail below. The present invention may be more clearly understood through the following embodiments, but these embodiments are merely for illustrative purposes only and are not intended to limit the scope of the present invention.

[0048] Preparation Example 1

[0049] Cerium nitrate hexahydrate (Ce(NO3)) in the preparation of a copper-cerium-yttrium solid solution catalyst for the decomposition and removal of nitrous oxide 3· 6H2O) and yttrium nitrate hexahydrate (Y(NO3) 3·A cerium-yttrium aqueous solution was prepared by quantifying 6H2O in an amount equal to the molar ratio of the cerium precursor to the yttrium precursor relative to a total of 0.1 M and dissolving it in distilled water. At this time, the molar ratio of the cerium precursor to the yttrium precursor was prepared to be 0.9:0.1. Subsequently, 0.5 M nitric acid (HNO3) was added to the cerium-yttrium aqueous solution to adjust the pH of the cerium-yttrium aqueous solution to 2.0 (±0.1). Next, 0.15 M citric acid (C6H8O7), which is 1.5 times the 0.1 M cerium-yttrium precursor, was quantified, and the cerium-yttrium aqueous solution was heated to 60°C or higher to dissolve it, thereby preparing a cerium-yttrium mixed slurry (first slurry). After removing moisture using a vacuum rotary evaporator, the mixture was sufficiently dried for more than one day in a dryer at 103°C to completely remove moisture contained in the micropores. Subsequently, a cerium-yttrium support was prepared by calcining in a convection furnace at a temperature of 500°C for 5 hours under an air atmosphere. Subsequently, copper nitrate trihydrate (Cu(NO3)23H2O) was quantified to be 10 wt% Cu based on the catalyst weight, and then dissolved in distilled water to prepare a copper aqueous solution. Next, an aqueous copper solution was mixed with a cerium-yttrium carrier to form a slurry (second slurry), and then moisture was removed using a vacuum rotary evaporator. To completely remove moisture contained in the micropores, the mixture was dried sufficiently for more than one day in a dryer at 103°C. Subsequently, the solid solution catalyst “10Cu / 0.9Ce0.1Y” was prepared by calcining in a convection furnace at a temperature of 500°C for 5 hours under an air atmosphere. In “10Cu / 0.9Ce0.1Y”, 10Cu represents 10 wt% copper, and 0.9Ce0.1Y represents a molar ratio of cerium to yttrium of 0.9:0.1.

[0050] Preparation Example 2

[0051] A solid solution catalyst “10Cu / 0.5Ce0.5Y” was prepared in the same manner as in Preparation Example 1, except that the molar ratio of the cerium precursor to the yttrium precursor was prepared as 0.5:0.5 during the preparation process of the cerium-yttrium aqueous solution of Preparation Example 1. In “10Cu / 0.5Ce0.5Y”, 10Cu means 10 wt% copper, and 0.5Ce0.5Y means that the molar ratio of cerium to yttrium is 0.5:0.5.

[0053] Preparation Example 3

[0054] A solid solution catalyst “10Cu / 0.1Ce0.9Y” was prepared in the same manner as in Preparation Example 1, except that the molar ratio of the cerium precursor to the yttrium precursor was prepared as 0.1:0.9 in the process of preparing the cerium-yttrium aqueous solution of Preparation Example 1. In “10Cu / 0.1Ce0.9Y”, 10Cu means 10 wt% copper, and 0.1Ce0.9Y means that the molar ratio of cerium to yttrium is 0.1:0.9.

[0056] Comparative Manufacturing Example 1

[0057] A solid solution catalyst “10Cu / 1.0Ce0Y” was prepared in the same manner as in Preparation Example 1, except that yttrium was not added during the process of preparing the cerium-yttrium aqueous solution of Preparation Example 1. In “10Cu / 1.0Ce0Y”, 10Cu means 10 wt% copper, and 1.0Ce0Y means that the molar ratio of cerium to yttrium is 1.0:0.

[0059] Comparative Manufacturing Example 2

[0060] A solid solution catalyst “5Cu / 0.5Ce0.5Y” was prepared in the same manner as in Preparation Example 2, except that in the copper addition process of Preparation Example 2, an aqueous copper solution was prepared using a copper content of 5 wt% based on the weight of the catalyst. In “5Cu / 0.5Ce0.5Y”, 5Cu means 5 wt% copper, and 0.5Ce0.5Y means that the molar ratio of cerium to yttrium is 0.5:0.5.

[0062] Comparative Manufacturing Example 3

[0063] A solid solution catalyst “15Cu / 0.5Ce0.5Y” was prepared in the same manner as in Preparation Example 2, except that in the copper addition process of Preparation Example 2, an aqueous copper solution was prepared using a copper content of 15 wt% based on the weight of the catalyst. In “15Cu / 0.5Ce0.5Y”, 15Cu means 15 wt% of copper, and 0.5Ce0.5Y means that the molar ratio of cerium to yttrium is 0.5:0.5.

[0065] Comparative Manufacturing Example 4

[0066] A solid solution catalyst “10Cu / 0.5Ce0.5Y (300)” was prepared in the same manner as in Preparation Example 2, except that during the calcination process of the cerium-yttrium carrier of Preparation Example 2, it was calcined in a convection furnace at a temperature of 300°C. In “10Cu / 0.5Ce0.5Y (300)”, 10Cu means 10 wt% copper, 0.5Ce0.5Y means that the molar ratio of cerium to yttrium is 0.5:0.5, and (300) means that it was calcined at a temperature of 300°C.

[0068] Comparative Manufacturing Example 5

[0069] A solid solution catalyst “10Cu / 0.5Ce0.5Y (400)” was prepared in the same manner as in Preparation Example 2, except that during the calcination process of the cerium-yttrium carrier of Preparation Example 2, it was calcined in a convection furnace at a temperature of 400°C. In “10Cu / 0.5Ce0.5Y (400)”, 10Cu means 10 wt% copper, 0.5Ce0.5Y means that the molar ratio of cerium to yttrium is 0.5:0.5, and (400) means that it was calcined at a temperature of 400°C.

[0071] Comparative Manufacturing Example 6

[0072] A solid solution catalyst “10Cu / 0.5Ce0.5Y (600)” was prepared in the same manner as in Preparation Example 2, except that during the cerium-yttrium carrier calcination process of Preparation Example 2, it was calcined at a temperature of 600°C in a convection furnace. In “10Cu / 0.5Ce0.5Y (600)”, 10Cu means 10 wt% copper, 0.5Ce0.5Y means that the molar ratio of cerium to yttrium is 0.5:0.5, and (600) means that it was calcined at a temperature of 600°C.

[0074] Comparative Manufacturing Example 7

[0075] A solid solution catalyst “10Cu / 0.5Ce0.5Y (700)” was prepared in the same manner as in Preparation Example 2, except that the cerium-yttrium carrier of Preparation Example 2 was calcined at a temperature of 700°C in a convection furnace during the calcination process. In “10Cu / 0.5Ce0.5Y (600)”, 10Cu means 10 wt% copper, 0.5Ce0.5Y means that the molar ratio of cerium to yttrium is 0.5:0.5, and (700) means that it was calcined at a temperature of 700°C.

[0076] The catalyst compositions according to the manufacturing examples and comparative manufacturing examples described above are shown in Table 1 below.

[0077] division Copper content (weight%) Molar ratio Cerium-Yttrium Carrier Calcination Temperature (°C) catalyst cerium yttrium Preparation Example 1 10 0.9 0.1 500 10Cu / 0.9Ce0.1Y Preparation Example 2 10 0.5 0.5 500 10Cu / 0.5Ce0.5Y Preparation Example 3 10 0.1 0.9 500 10Cu / 0.1Ce0.9Y Comparative Manufacturing Example 1 10 1.0 - 500 10Cu / 1.0Ce0Y Comparative Manufacturing Example 2 5 0.5 0.5 500 5Cu / 0.5Ce0.5Y Comparative Manufacturing Example 3 15 0.5 0.5 500 15Cu / 0.5Ce0.5Y Comparative Manufacturing Example 4 10 0.5 0.5 300 10Cu / 0.5Ce0.5Y(300) Comparative Manufacturing Example 5 10 0.5 0.5 400 10Cu / 0.5Ce0.5Y(400) Comparative Manufacturing Example 6 10 0.5 0.5 600 10Cu / 0.5Ce0.5Y(600) Comparative Manufacturing Example 7 10 0.5 0.5 700 10Cu / 0.5Ce0.5Y(700)

[0078] Example 1

[0079] In order to confirm the nitrous oxide decomposition and removal efficiency according to the copper addition content in the preparation of the copper-cerium-yttrium solid solution catalyst of the present invention, the conversion rate of nitrous oxide was measured for the catalysts prepared according to Preparation Example 2 and Comparative Preparation Examples 2 and 3, and the results are shown in Figure 2 below. The experimental conditions and measurement methods are as follows, and are the same in Examples 2, 3 and 7 described later.

[0081] [Experimental Conditions]

[0082] The gas injected into the catalytic reactor is in the gaseous phase under an air atmosphere, with a nitrous oxide concentration of 450 ppm and a nitric oxide concentration of 200 ppm (Example 7), an inflow rate of 500 cc / min, and a space velocity of 60,000 hr -1 The experiment was conducted at a temperature range of 300 to 500°C. For reference, space velocity is an indicator representing the amount of target gas that can be treated by the catalyst, expressed as the ratio of the volume of the catalyst to the total gas flow rate.

[0084] [measurement method]

[0085] The gaseous nitrous oxide conversion rate was calculated according to the following mathematical formula 1. In addition, the nitrous oxide is calculated by measuring the concentration of the injected gaseous unreacted nitrous oxide using a non-dispersive infrared gas analyzer (ZKJ-2, Fuji Electric Co.).

[0087] <Mathematical Formula 1>

[0088]

[0090] Looking at the nitrous oxide removal rates of Preparation Example 2 and Comparative Preparation Examples 2 and 3 from FIG. 2, it can be confirmed that Preparation Example 2 and Comparative Preparation Example 3, which have a higher copper content compared to Comparative Preparation Example 2, have an enhanced effect on low-temperature nitrous oxide decomposition and removal performance. In particular, it can be confirmed that when a 10 wt% Cu catalyst is prepared based on the weight of the catalyst in Preparation Example 2, an even superior nitrous oxide conversion rate is exhibited in the 450~500℃ range.

[0092] Example 2

[0093] Based on the results of Example 1, an experiment was conducted to determine the effect of various cerium-yttrium carrier calcination temperatures on the nitrous oxide conversion rate, and the results are shown in Figure 3 below. The experimental conditions were carried out in the same manner as in Example 1 described above, and the catalysts used were Preparation Example 2 and Comparative Preparation Examples 4 to 7, depending on the cerium-yttrium carrier calcination temperature.

[0094] From FIG. 3, different nitrous oxide decomposition and removal performances were observed in the copper-cerium-yttrium solid solution catalysts of Preparation Example 2 and Comparative Preparation Examples 4 to 7 as the calcination temperature of the cerium-yttrium carrier was changed. In particular, it can be confirmed that the catalyst calcined at 400 to 600°C with the cerium-yttrium carrier based on the catalysts of Preparation Example 2 and Comparative Preparation Examples 5 and 6 exhibits a superior nitrous oxide conversion rate in the temperature range of 450 to 500°C.

[0096] Example 3

[0097] Based on the results of Examples 1 and 2, an experiment was conducted to determine the effect of various molar ratios of cerium-yttrium carriers on the nitrous oxide conversion rate, and the results are shown in Figure 4 below. The experimental conditions were carried out in the same manner as in Example 1 described above, and the catalysts used were Preparation Examples 1 to 3 and Comparative Preparation Example 1, prepared according to the molar ratio of cerium-yttrium carriers.

[0098] From FIG. 4, it can be seen that differences in nitrous oxide conversion rates occur depending on the molar ratio of the cerium-yttrium support in the copper-cerium-yttrium solid solution catalysts of Preparation Examples 1 to 3 and Comparative Preparation Example 1. In the case of Preparation Examples 1 to 3, in which yttrium was added to Comparative Preparation Example 1, all showed enhanced nitrous oxide conversion rates. In particular, it was confirmed that Preparation Example 2, prepared with a molar ratio of cerium precursor to yttrium precursor of 0.5:0.5, exhibited the best nitrous oxide conversion rate in the temperature range of 450 to 500°C, while Preparation Example 3, prepared with a molar ratio of cerium precursor to yttrium precursor of 0.1:0.9, showed a decreased nitrous oxide conversion rate as the molar ratio of yttrium increased.

[0100] Example 4

[0101] Based on the results of Example 3, an X-ray diffractometer was used to analyze the effect of the molar ratio of the cerium-yttrium support on the structural characteristics of the copper-cerium-yttrium solid solution catalyst, and the resulting X-ray diffraction patterns are shown in Fig. 5. The catalysts used were Preparation Examples 1 to 3 and Comparative Preparation Example 1, prepared according to the molar ratio of the cerium-yttrium support. Referring to Fig. 5, in Preparation Examples 1 to 3 and Comparative Preparation Example 1, the copper oxide existed as monoclinic CuO as a bulk species, and the oxygen oxide existed as cubic CeO2. In Preparation Examples 1, 2 and Comparative Preparation Example 1, single CuO structure and CeO2 structure peaks were observed, whereas no peak for the Y2O3 structure was observed. On the other hand, in Preparation Example 3, a Y2O3 lattice was observed instead of a CeO2 lattice. This is interpreted as the excessive amount of Y2O3 causing cerium atoms to dissolve within the Y2O3 lattice instead of maintaining the CeO2 lattice, and a peak shift was observed due to the solid solution.

[0102] To analyze the crystal structure of the metal oxides more clearly, the selected area electron diffraction (SAED) patterns of Preparation Examples 1 to 3 and Comparative Preparation Example 1 were analyzed, and in FIG. 6, the CuO plane is shown in red, the Cu2O plane in orange, the Y2O3 plane in yellow, the CeO2 plane in green, and the Ce2O3 plane in blue. Referring to FIG. 6, planes of cubic Ce2O3 and cubic Cu2O, which were not observed in the X-ray diffraction (XRD) pattern of FIG. 5, were observed. Similar to the X-ray diffraction (XRD) pattern of FIG. 5, the CeO2 phase was dominant in Preparation Examples 1 and 2 and Comparative Preparation Example 1. On the other hand, in Preparation Example 3, it was observed that the structure consisted of a Y2O3 lattice instead of CeO2. This is interpreted to mean that, similar to the X-ray diffraction pattern (XRD pattern) in Fig. 5 above, the CeO2 lattice cannot perform the role of a solvent when an excessive amount of Y2O3 is added.

[0104] Example 5

[0105] Based on the results in Example 3, the catalysts prepared according to Preparation Examples 1 to 3 and Comparative Preparation Example 1 were separated by the Gaussian-Lorentzian method, and the XPS results of O 1s were analyzed to determine the surface-adsorbed oxygen species (O) present on the catalyst surface. V ) is illustrated in Fig. 7. Referring to the results in Fig. 7, Comparative Example 1 shows a surface adsorbed oxygen species ratio of 15.7%, Example 1 shows 22.8%, Example 2 shows 42.4%, and Example 3 shows 50.8%. Comparative Example 1, which does not contain yttrium, showed a relatively low surface adsorbed oxygen species ratio of 15.7%, whereas Example 3, which contains the most yttrium, showed a high surface adsorbed oxygen species ratio of 50.8%.

[0106] Next, the types and distribution ratios of cerium oxides present on the catalyst surface were illustrated in FIG. 8 through the XPS analysis results of Ce 3d for the catalysts prepared according to Preparation Examples 1 to 3 and Comparative Preparation Example 1, using the same method as the XPS analysis described above. Referring to the results in FIG. 8, among the cerium oxides, the cerium (Ce 3d) corresponding to an oxidation value of +3 relative to the total cerium... 3+ The ratios of ) are in the order of Preparation Example 3 (17.7%) > Preparation Example 2 (15.4%) > Preparation Example 1 (13.0%) > Comparative Preparation Example 1 (10.8%). Comparative Preparation Example 1, which does not contain yttrium, showed a relatively low ratio of cerium with an oxidation value of +3 to total cerium of 10.8%, whereas Preparation Example 3, which contains the most yttrium, showed a high ratio of cerium with an oxidation value of +3 to total cerium of 17.7%.

[0107] Next, the types and distribution ratios of copper oxides present on the catalyst surface were illustrated in FIG. 9 through the XPS analysis results of Cu 2p for the catalysts prepared according to Preparation Examples 1 to 3 and Comparative Preparation Example 1, using the same method as the XPS analysis described above. Referring to the results in FIG. 9, among the copper oxides, copper (Cu) corresponding to an oxidation value of +2 relative to the total copper 2+ The ratios of ) are in the order of Preparation Example 3 (62.4%) > Preparation Example 2 (61.5%) > Preparation Example 1 (37.4%) > Comparative Preparation Example 1 (13.3%). Comparative Preparation Example 1, which does not contain yttrium, showed a relatively low ratio of copper with an oxidation value of +2 to total copper of 13.3%, whereas Preparation Example 3, which contains the most yttrium, showed a high ratio of copper with an oxidation value of +2 to total copper of 62.4%.

[0108] Based on the XPS analysis results in Example 5 above, it is interpreted that in the case of Preparation Examples 1 to 3 and Comparative Preparation Example 1, a CeO2-Y2O3 solid solution was formed in Preparation Example 3, which contained the most yttrium, and the ratio of surface-adsorbed oxygen species to total oxygen species was observed to be the highest in Fig. 7, the ratio of cerium corresponding to an oxidation value of +3 to total cerium was observed to be the highest in Fig. 8, and the ratio of copper corresponding to an oxidation value of +2 to total copper was observed to be the highest in Fig. 9.

[0110] Example 6

[0111] Based on the results of Example 3, O2-TPD (temperature programmed desorption) analysis was performed to confirm the adsorption and desorption characteristics of the catalysts prepared according to Preparation Examples 1 to 3 and Comparative Preparation Example 1, and the results are shown in Fig. 10. Referring to the results in Fig. 10, it was observed that oxygen was first desorbed at 220°C for Comparative Preparation Example 1, 230°C for Preparation Example 1, 330°C for Preparation Example 2, and 390°C for Preparation Example 3. In the case of Comparative Preparation Example 1, which did not contain yttrium, oxygen was desorbed at a relatively low temperature of 220°C, whereas in the case of Preparation Example 3, which contained the most yttrium, oxygen was desorbed at a relatively high temperature of 390°C. This is interpreted as having a negative effect on the nitrous oxide decomposition reaction in the case of Preparation Example 3, which contains the most yttrium, because Y2O3 improves oxygen storage capacity, causing an increase in oxygen vacancies, which induces a strong affinity for oxygen, and makes it difficult for the catalyst to desorb oxygen species during the reaction step.

[0112] Subsequently, H2-TPR (temperature programmed reduction) analysis was performed to confirm the redox characteristics of Preparation Examples 1 to 3 and Comparative Preparation Example 1, and the results are shown in Fig. 11. Referring to the results in Fig. 11, the main reduction peaks of Preparation Examples 1 to 3 and Comparative Preparation Example 1 were observed at temperatures between 100 and 400°C; the first 'α' peak is the reduction peak of finely dispersed CuO due to strong interaction with CeO2, the second 'β' peak is the reduction peak of CuO weakly bound to CeO2, and the third 'γ' peak is Cu, such as isolated bulk CuO. 2+ It is the reduction peak of the weak conjugate containing ions. In the case of Preparation Example 3, which contains the most yttrium, the highest Cu in the result of Fig. 9. 2+ Due to the ratio, the largest area of ​​the 'α' peak and the highest maximum peak reduction temperature were observed. Subsequently, regarding the 'β' peak, it was observed that in Preparation Examples 1 to 3 and Comparative Preparation Example 1, the interaction between copper and cerium weakened as the yttrium addition content increased, causing the 'β' peak to decrease; in Preparation Examples 2 and 3, which had high yttrium addition content, the 'β' peak was observed to disappear. Furthermore, regarding the maximum peak reduction temperature of the 'γ' peak, the order was Preparation Example 3 (320℃) > Comparative Preparation Example 1 (300℃) > Preparation Example 2 (250℃) > Preparation Example 1 (240℃). This indicates that in the case of Preparation Example 2, the appropriate addition of yttrium, consistent with Fig. 9, [causes] the Cu on the catalyst surface 2+ It is interpreted that the reduction temperature of CuO was lowered by enriching it, facilitating oxygen movement in CeO2 at low temperatures, and improving redox characteristics and oxygen vacancy formation.

[0114] Example 7

[0115] Since nitrous oxide and nitric oxide are generated simultaneously during the production process of nitric acid and adipic acid and the combustion of ammonia fuel, based on the results of Example 3, the conversion rate of nitrous oxide was measured for the catalyst prepared according to Preparation Example 2 in order to confirm the influence of nitric oxide on the decomposition and removal of nitrous oxide, and the results are shown in Figure 12 below. The experimental conditions were carried out in the same manner as in Example 1 described above.

[0116] From FIG. 12, different nitrous oxide decomposition and removal performances were exhibited by additionally injecting gaseous nitric oxide into the copper-cerium-yttrium solid solution catalyst of Preparation Example 2. When 200 ppm of nitric oxide was injected, the copper-cerium-yttrium solid solution catalyst of Preparation Example 2 exhibited a nitrous oxide conversion rate of over 70% at 450°C. In the direct decomposition reaction of nitrous oxide, it is known that nitric oxide competitively adsorbs to the catalyst along with nitrous oxide, thereby hindering the adsorption of nitrous oxide and lowering the nitrous oxide conversion rate. This is interpreted as the copper-cerium-yttrium solid solution catalyst of Preparation Example 2 exhibiting durability against nitric oxide by providing adsorption sites for nitrous oxide due to the abundant oxygen vacancies.

[0118] Although embodiments of the present invention have been described above with reference to the attached drawings, those skilled in the art will understand that the present invention may be implemented in other specific forms without changing its technical concept or essential features. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive.

Claims

Claim 1 A solid solution catalyst for decomposing nitrous oxide comprising copper, cerium, and yttrium in oxide form, wherein the molar ratio of cerium to yttrium is 1:9 to 9:1, the copper is included at 1 to 20 weight% relative to the total weight of the catalyst, and the ratio of surface-adsorbed oxygen species relative to the total oxygen atoms present on the surface of the catalyst is 40% to 100% as measured by XPS analysis. Claim 2 A solid solution catalyst according to claim 1, wherein the copper oxide is at least one of CuO, Cu2O, and CuO2, and the ratio of copper atoms corresponding to an oxidation value of +2 relative to the total number of copper atoms included in the catalyst is 60% to 100% as measured by XPS analysis. Claim 3 A solid solution catalyst according to claim 1, wherein the oxide of cerium is at least one of CeO2 and Ce2O3, and the ratio of cerium atoms corresponding to an oxidation value of +3 relative to the total number of cerium atoms contained in the catalyst is 15% to 100% as measured by XPS analysis. Claim 4 delete Claim 5 In claim 1, the yttrium oxide is a solid solution catalyst of Y2O3. Claim 6 A step of preparing a cerium-yttrium aqueous solution by dissolving a cerium precursor and an yttrium precursor in distilled water such that the molar ratio of cerium to yttrium is 1:9 to 9:1; a step of adding nitric acid to the cerium-yttrium aqueous solution to adjust the pH of the cerium-yttrium aqueous solution to 1.9 to 2.1; a step of preparing a first slurry by adding citric acid to the cerium-yttrium aqueous solution and performing a heating process; a step of preparing a cerium-yttrium carrier by drying the first slurry and performing a first calcination process; a step of preparing a copper aqueous solution by dissolving a copper precursor in distilled water; and a step of preparing a second slurry by adding the cerium-yttrium carrier to the copper aqueous solution and mixing. A method for preparing a nitrous oxide decomposition solid solution catalyst comprising the step of drying the second slurry and performing a second calcination process, wherein copper, cerium, and yttrium are each included in oxide form, and the ratio of surface-adsorbed oxygen species to total oxygen atoms is 40% to 100% as measured by XPS analysis. Claim 7 A method for preparing a nitrous oxide decomposition solid solution catalyst according to claim 6, wherein the copper precursor is provided such that the copper is included in an amount of 1 to 20 weight percent relative to the total weight of the catalyst. Claim 8 A method for manufacturing a nitrous oxide decomposition solid solution catalyst according to claim 6, wherein at least one of the first calcination and the second calcination is carried out in an air atmosphere at a temperature of 200 to 800°C for 2 to 8 hours. Claim 9 In claim 6, the copper precursor is copper nitrate trihydrate (Cu(NO3) 2· 3H2O), kappa sulfate (CuSO4), kappa chloride (CuCl2), kappa oxide (CuO), kappa sulfate pentahydrate (CuSO4 4· 5H2O), kappa hydroxide (Cu(OH)2), kappa chloride dihydrate (CuCl 2· 2H2O), kappa acetate (Cu(CO2CH3)2) and kappa nitrate hydrate (Cu(NO3) 2· A method for preparing a nitrous oxide decomposition solid solution catalyst that is at least one of xH2O. Claim 10 In claim 6, the cerium precursor is cerium nitrate hexahydrate (Ce(NO3) 3· 6H2O), cerium chloride (CeCl3), cerium sulfate (Ce2(SO4)3), cerium oxalate hydrate (Ce2(C2O4) 3· xH2O), cerium acetate hydrate (Ce(CH3CO2) 3· xH2O), cerium hydroxide (Ce(OH)4), cerium oxide (CeO2) and cerium carbonate hydrate (Ce2(CO3)) 3· A method for preparing a nitrous oxide decomposition solid solution catalyst that is at least one of xH2O. Claim 11 In claim 6, the yttrium precursor is nitrate hexahydrate (Y(NO3) 3· 6H2O), yttrium chloride (YCl3), yttrium acetate hydrate ((CH3CO2)3Y · xH2O), yttrium nitrate tetrahydrate (Y(NO3) 3· 4H2O), yttrium oxide (Y2O3) and yttrium chloride hexahydrate (YCl 3· A method for preparing a nitrous oxide decomposition solid solution catalyst that is at least one of 6H2O.

Citation Information

Patent Citations

  • Nitrous oxide decomposition catalyst and its manufacturing method

    KR102493409B1